Trophic Level Analysis of Eretan Coastal Waters, Indramayu Regency, West Java Province - Zainalarifin, Jauhar; Effendi, Hefni; Mashar, Ali; Aprilia, Mita (Universitas Diponegoro, 2025)
The coastal waters of Eretan located in the north of Indramayu Regency are used as fishing grounds by local fishermen. The condition of water input, especially from the surrounding river waters, namely the Cimanuk River, Cipunagara River, and Perawan River, is thought to affect the condition of coastal waters. This study aims to analyze the trophic level based on water quality conditions. Data collection on the quality of the aquatic environment was carried out in three locations with purposive sampling considerations, namely the Cipunagara estuary, the Perawan estuary, and the Cimanuk estuary. Sampling was carried out in two different seasons, namely the dry season and the rainy season. The method used in the analysis is the TRIX Index based on nutrients, phosphate, chlorophyll-α, and DO saturation. Meanwhile, water quality parameters at each location were analyzed using principal component analysis (PCA). The results of the study showed that the main water quality parameters tended to differ in each season. The trophic level at the three locations had values between 4.99 and 8.59, so they had mesotrophic to hypertrophic status. This shows that coastal water conditions need to be managed so that water conditions are more stable.